PERILAKU DAN KEPUTUSAN PEMBELIAN KONSUMEN RESTORAN MELALUI STIMULUS 50% DISCOUNT DI SURABAYA - Hatane Semuel; Annette Veronica Kosasih; Hellen Novia (Jurnal Manajemen Pemasaran, 2007)
The use of ”50% discount” promotion is an interesting phenomenom in retail business, especially as one of the marketing strategies within the company. It can also be used as a stimulus towards customer purchase decision. This research is trying to see the impact of the stimulus towards the customer purchase decision when they dine in restaurants in Surabaya. This customer behavior is studied from the factors influencing that behavior, such as social, personal, psychological and cultural factors; whereas the customer purchase decision is studied from the decision making process, which is decided into fully planned purchase, partially planned purchase and unplanned purchase. The result of the research, which is taken from 100 respondents, shows that ”50% discount” stimulus from social, psychological and factors have positive influences significantly towards the customer purchase desision. Whereas, from cultural and personal factors, it has no influence on the customer purchase decision. Abstract in Bahasa Indonesia: Penggunaan promosi “50% Discount” merupakan sebuah fenomena yang menarik di kalangan bisnis ritel, sebagai salahsatu strategi pemasaran perusahaan. Penggunaaan strategi pemasaran dengan 50% Discount di restoran dapat menjadi stimulus terhadap keputusan pembelian konsumen. Penelitian ini mencoba melihat pengaruh stimulus tersebut terhadap perilaku pengambilan keputusan pembelian konsumen restoran di Surabaya. Perilaku konsumen diamati melalui faktor-faktor yang mempengaruhi perilaku tersebut, yaitu faktor sosial, faktor personal, faktor psychological, dan faktor cultural, sedangkan keputusan pembelian diamati melalui bentuk proses pengambilan keputusan pembelian, dan digolongkan dalam Fully Planned Purchase, Partially Planned Purchase, dan Unplanned Purchase. Hasil penelitian dari 100 responden menunjukan bahwa stimulus “50% Discount”yang diberikan melalui faktor sosial dan psychological berpengaruh positif significan terhadap perilaku pengambilan keputusan, sedangkan faktor culture dan faktor personal tidak berpengaruh terhadap perilaku pengambilan keputusan pembelian konsumen. Kata kunci: perilaku konsumen, 50% discount, keputusan pembelian, restoran.